Description of the Martian Polar Cap Breeze - Fernández Rojas, Walter (1995)
The surface temperature of the Martian polar caps is about 148 K (frost point temperature of CO2 at a surface pressure of about 6 hPa), with the "desert" (frost-free) areas adjacent to the polar caps having much greater surface temperatures. The existence of this steep meridional gradient of temperature between the polar caps and the adjacent "desert" areas may produce in the atmosphere a baroclinic instability which generates an atmospheric circulation system similar in some aspects to the terrestrial sea breeze. We have called this circulation system the Martian polar cap breeze. In this paper, the phenomenology of the Martian polar cap breeze is developed on the basis of the indirect observational evidence. Along with friction and the Coriolis force, other factors influence the polar cap breeze: the prevailing wind, topography, irregularity of the polar cap-edge, and stability of the atmosphere. These factors are studied in a qualitative form, as weil as the seasonal variations. In addition, the large-scale polar cap wind is presented as a different Martian atmospheric circulation system.